(untitled) (Research, Society and Development, 2021)
Brazil has a prevalence of 1.3% disabled people. Regarding the physical impairments related to neurological pathologies, they generate functional disability worldwide. Thus, this work aimed to carry out scientific and technological research on research on the use of focal vibration associated with wearable mobile devices in individuals with motor impairments resulting from neurological pathologies. In the search for patents the bases were used: Espacenet, INPI, USPTO and Web of Science; and articles in the databases: Scielo, Scopus, Science Direct, Web of Science, Pubmed, from 1967 to 2020. The results of the search for patents in the mentioned context were negative, and in relation to the articles, significant results were obtained with 667 publications in the Science Direct with a peak of publication in 2018. It was observed then, that new studies must be carried out to promote the properties and effectiveness of the focal vibration, and to promote incentives to the development and technological and scientific productions.